The implementation of the PNC, Youth Civic Action Program its implication for Thailand's educational system - Gajasane, Yupinphan 1949- ([Quezon City s.n.], 1974)
Data were gathered through interviews with the supervisors implementing the Youth Civic Action Program (YCAP) of the Philippine Normal College and questionnaires accomplished by 250 third year college students who took part in YCAP in the summer of 1972-1973. Among the projects undertaken by YCAP participants are (1) self-sufficiency, (2) community beautification, (3) environmental sanitation, (4) sport and other physical fitness development, (5) education, (6) health and (7) cultural enrichment. More than three-fourths of the participants think that the required number of hours spent in YCAP activities is just right.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Philippine Normal College; Youth Civic Action Program; Education -- Thailand